Pengetahuan Keluarga Pasien Dalam Pencegahan Tubercolosis Paru: Studi Cross-Sectional - Deswita, Reny; Andreyani, Luki; Sekarsari, Rita; Haerani, Beti (Journal of Pubnursing Sciences, 2024)
Background: Tuberculosis (TB) is a chronic infectious disease that is the second leading cause of death in the world, resulting in 1.3 million deaths with TB in 2022. Tangerang Regency has the highest burden of TB cases in Banten Province. Knowledge about preventing tuberculosis transmission greatly influences actions in preventing TB transmission to family members. Objective: To identify the relationship between the level of knowledge of patient families and efforts to prevent pulmonary tuberculosis in the Gunung Kaler Health Center work area. Method: Quantitative research with a cross-sectional design. A total of 60 respondents were recruited using a purposive sampling technique. Data analysis using Chi Square. Results: The majority of respondents had good knowledge and prevention efforts, as many as 32 (69.9%). There was a significant relationship between patient family knowledge and efforts to prevent pulmonary TB (p value <0.005). Conclusion: Good family knowledge will increase efforts to prevent pulmonary TB in the family.